Muhammadiyah dan Kebudayaan - Apiek Linova; Qori Ainnun Astuti (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study examines the relationship between Muhammadiyah and culture within the context of contemporary Indonesian society. Muhammadiyah has often been perceived as an Islamic reform movement that emphasizes religious purification and rationality, generating ongoing debates regarding its stance toward local cultural traditions. This study aims to analyze how Muhammadiyah conceptualizes, responds to, and engages with culture amid social change and pluralism. Employing a qualitative approach through library research, this article analyzes recent scholarly publications since 2020 that discuss Muhammadiyah, cultural da‘wah, and the concept of progressive Islam. Data were collected from peer-reviewed journal articles and analyzed using interpretative content analysis to identify key themes, patterns, and shifts in perspective. The findings indicate that Muhammadiyah’s approach to culture has evolved from a predominantly purificatory orientation toward a more dialogical and contextual framework, particularly through the development of cultural da‘wah strategies and the use of modern media. This shift reflects Muhammadiyah’s effort to maintain theological integrity while enhancing social relevance in a multicultural environment. The study concludes that Muhammadiyah’s relationship with culture is selective and critical, characterized by the acceptance, reinterpretation, and transformation of cultural elements in accordance with Islamic values. This dynamic engagement positions Muhammadiyah not only as a religious movement but also as a cultural actor contributing to the formation of a rational, inclusive, and progressive Islamic society. Keywords: Muhammadiyah; Culture; Cultural Da‘wah; Progressive Islam; Indonesia AbstrakPenelitian ini mengkaji hubungan antara Muhammadiyah dan kebudayaan dalam konteks masyarakat Indonesia kontemporer. Muhammadiyah kerap dipersepsikan sebagai gerakan reformasi Islam yang menekankan pemurnian ajaran dan rasionalitas, sehingga memunculkan perdebatan yang berkelanjutan mengenai sikapnya terhadap tradisi budaya lokal. Penelitian ini bertujuan untuk menganalisis bagaimana Muhammadiyah mengonseptualisasikan, merespons, dan berinteraksi dengan kebudayaan di tengah dinamika perubahan sosial dan pluralisme. Dengan menggunakan pendekatan kualitatif melalui studi kepustakaan, artikel ini menganalisis publikasi ilmiah terkini sejak tahun 2020 yang membahas Muhammadiyah, dakwah kultural, dan konsep Islam progresif. Data dikumpulkan dari artikel jurnal bereputasi dan dianalisis menggunakan analisis isi interpretatif untuk mengidentifikasi tema-tema utama, pola, serta pergeseran perspektif. Hasil penelitian menunjukkan bahwa pendekatan Muhammadiyah terhadap kebudayaan telah berkembang dari orientasi yang dominan bersifat purifikatif menuju kerangka yang lebih dialogis dan kontekstual, khususnya melalui pengembangan strategi dakwah kultural dan pemanfaatan media modern. Pergeseran ini mencerminkan upaya Muhammadiyah dalam menjaga integritas teologis sekaligus meningkatkan relevansi sosialnya dalam lingkungan multikultural. Penelitian ini menyimpulkan bahwa relasi Muhammadiyah dengan kebudayaan bersifat selektif dan kritis, yang ditandai dengan penerimaan, reinterpretasi, serta transformasi unsur-unsur budaya sesuai dengan nilai-nilai Islam. Keterlibatan yang dinamis ini menempatkan Muhammadiyah tidak hanya sebagai gerakan keagamaan, tetapi juga sebagai aktor kebudayaan yang berkontribusi dalam pembentukan masyarakat Islam yang rasional, inklusif, dan progresif. Kata kunci: Muhammadiyah; Kebudayaan; Dakwah Kultural; Islam Progresif; Indonesia